The Role of Volunteering in Higher Education – the Manifestation of Coaching as Volunteer Activity at Kaposvár University - Walter, Imola Ágnes (Acta Scientiarum Socialium, 2015)
The Role of Volunteering in Higher Education – the Manifestation of Coaching as Volunteer Activity at Kaposvár University Since The International Year of Volunteers (2001), volunteering has gained significance in Hungary. Apart from being a decision made by the individual, its regulation has become a function of the government. According to the principle of Magyarországi Önkéntes Stratégia 2011-2020 (The Hungarian Strategy of Volunteering 2011-2020), it should be a goal of each individual to take part in volunteer activity. The above document makes volunteering compulsory for secondary school students. Although it is optional for adults, the document states that it should become part and parcel of teacher training until 2017. In order to achieve the full integration of volunteering into higher education, with other words to quantify it by making it measurable within the credit system, further provisions are needed which take into account the organization and management of higher education.
Keywords: Volunteering; Participate; Lifelong Learning Programme; Adult learning